PENGARUH VARIASI LAMA KONTAK FITOREMEDIASI TANAMAN KIAMBANG (SALVINIA MOLESTA) TERHADAP KADAR KADMIUM (Cd) PADA LIMBAH CAIR HOME INDUSTRY BATIK “X” MAGELANG - Zulfa Oktavia; Budiyono Budiyono; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Batik industry "X" has a potential to produce hazardous waste in the form of Cadmium (0.72 mg/L). It can cause environmental pollution if there is no wastewater  treatment plant. One of the methods which used to reduce the levels of Cd is phytoremediation using Salvinia molesta. The purpose of this study is to determine the effect of contact time variation by using Salvinia molesta towards the levels of Cd in liquid waste of batik. The type of research used  a quasi-experiment research with pretest-posttest with control design. The population in this research were the liquid waste of the batik which was produced from the batik’s dying process. The sample that used were 150 liters of  liquid waste of dying output that has diluted 25 % to 9 replications and 3 controls. The level of the Cd decline efficiency by using Salvinia molesta during 9 days contact time showed the highest decline 58.80%. From the Kruskal Wallis test,   significance value  of 0.0001 ( < 0.05) was obtained. The variation of the contact  time affected the value decreased levels of Cadmium (Cd). Continued test with  Mann Whitney concluded that there were significant differences in the average of cadmium level decrease by using Salvinia molesta in the variation of the contact time during 3 days to 6 days and 9 days. The conclusion of this study was the variation of the contact time using Salvinia molesta affected on decreased levels of Cd in liquid waste of batik X. Prolonged the contact time of the plant; therefore, the Cd levels of the liquid water will be lower.